Modified Shock Index to Predict In-Hospital Outcome among Patients Presenting with ST-Segment Elevation Myocardial Infarction - Asifudduza, Md.; Ahmed, Nazir; Faysal, Md. Owashak; Quadir, Rahatul; Ali, Sharmin; Hasan, Md. Rakibul; Islam, Nurul; Sultana, Sharmeen (Cardiology and Cardiovascular Medicine, 2023)
Background: Prompt identification of higher-risk patients presenting with ST-segment elevation myocardial infarction (STEMI) is crucial to pursue a more aggressive approach. Objective: To evaluate the Modified Shock Index (MSI), as a predictor of in-hospital outcome among patients with STEMI. Methods: This cross sectional observational study was carried out in the Department of Cardiology, National Heart Foundation Hospital and Research Institute, Mirpur, Dhaka from January 2020 to December 2020. A total of 100 patients were selected with acute STEMI admitted in the department of Cardiology, NHFH&RI, within the study period, who fulfilled the inclusion and exclusion criteria. Results: The mean age 55.6±10.2 years in Group I and 56.1±12.0 years in Group II. Male patients were predominant in both the groups. Regarding MSI 40(40.0%) patients had high admission MSI (≥0.91) and 60(60.0%) patients had normal admission MSI (<0.91). Regarding risk factors, hypertension, diabetes mellitus, smoking, dyslipidemia and family H/O CAD were not statistically significant (p>0.05) between the two groups. There was a significant (p<0.05) difference observed for NT-pro-BNP which was higher in group I than group II (77.5% vs 40.0%), but other investigations were not statistically significant (p>0.05) between the two groups. LVEF was found lower in Group I than group II (38.0±4.7 percent vs 42.6±5.2 percent), which was statistically significant (p<0.05) between the two groups. Regarding ECG findings 72.5% of patients were found with anterior MI in group I and 33.3% in group II, which was statistically significant (p<0.05) between the two groups. During the period of hospitalization patients in group I developed heart failure more than group II patients (67.5% vs 26.7%, p value=0.001). Development of cardiogenic shock was also significant in group I patients compared to group II patients (57.5% vs 1.7%, p value=0.001). Although the mortality rate was higher in group I patients, it was not significant between the two groups. Conclusion: Heart failure and cardiogenic shock were significantly higher in MSI ≥ 0.91 group in comparison to MSI < 0.91 group. MSI was shown to be a valuable bedside tool which can rapidly identify high-risk STEMI patients at presentation.